Knowledge sharing dynamics in international subcontracting arrangements : The case of Finnish high-tech SMEs - Ahokangas, Petri; Haapanen, Lauri; Golgeci, Ismail; Arslan, Ahmad; Khan, Zaheer; Kontkanen, Minnie (Elsevier, 2021)
This paper focuses on an under-researched topic of knowledge sharing dynamics in international subcontracting relationships of SMEs. Based on in-depth qualitative analysis of three Finnish high-tech firms, our findings reveal that not only cost and performance expectations motivate SMEs for international subcontracting, but also the factors like lack of in-house alternatives, the volatility of workload, and need for speed in growth-related activities such as deliveries play an important role. We further found that the SMEs try to balance internal risks/uncertainty and external risks/uncertainty throughout international subcontracting. Our paper contributes to the extant literature by being one of the first studies to specifically highlight the range of knowledge sharing and knowledge protection mechanisms used in international subcontracting in SME-SME relationships in which partners come from different institutional settings and physical locations. Moreover, this paper is one of the few studies to specifically highlight the role of time in knowledge sharing from the buyer's point of view as well, specifically by emphasizing the need to balance the internal and external risks during the life-cycle of international subcontracting while balancing short-term challenges and long-term strategic development plans.
Keywords: Finnish; International subcontracting; Knowledge sharing; SMEs; small and medium-sized enterprises; fi=Kansainvälinen liiketoiminta|en=International Business|